2015
DOI: 10.1128/genomea.01370-14
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Symbiotic and Nonsymbiotic Rhizopus microsporus Strains CBS 344.29 and ATCC 62417

Abstract: Specific Rhizopus microsporus pathovars harbor bacterial endosymbionts (Burkholderia rhizoxinica) for the production of a phytotoxin. Here, we present the draft genome sequences of two R. microsporus strains, one symbiotic (ATCC 62417), and one endosymbiont-free (CBS 344.29). The gene predictions were supported by RNA sequencing (RNA-seq) data. The functional annotation sets the basis for comparative analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“… species Whole cell susceptibility to VCZ a CYP51 gene ORF LDM Ref. Median (range) MIC (mg/L) (n strains tested) Designation b CYP51 family c total length (nt) total length (nt) total length (aa) aa in position 140 d R. arrhizus 16.00 (4.00 –>16.00) Ra CYP51 A F5 1755 1533 510 F 56 (n = 17) Ra CYP51 B F1 1755 1533 510 Y R. microsporus 16.00 (4.00–16.00) RmCYP51 A F1 1774 1533 510 Y 52 (n = 13) RmCYP51 B F5 1645 1539 508 F M. circinelloides 16.00 (16.00–>16.00) McCYP51 A F1 1773 1539 512 Y 57 (n = 18) McCYP51 B F5 1658 1533 510 F a VCZ susceptibility according to CLSI standard microbroth dilution method 54 ; ORF, open reading frame; LDM, lanosterol 14α-demethylase; MIC, minimum inhibitory concentration; b loci A and B were attributed according to identification with CYP51A and CYP51B of A. fumigatus strain AF293; P450 family name was attributed to each CYP51 paralogue according to Nelson’s database ( http://drnelson.utmem.edu/CytochromeP450.html ); d amino acid position 140 according to S. cerevisiae CYP51 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… species Whole cell susceptibility to VCZ a CYP51 gene ORF LDM Ref. Median (range) MIC (mg/L) (n strains tested) Designation b CYP51 family c total length (nt) total length (nt) total length (aa) aa in position 140 d R. arrhizus 16.00 (4.00 –>16.00) Ra CYP51 A F5 1755 1533 510 F 56 (n = 17) Ra CYP51 B F1 1755 1533 510 Y R. microsporus 16.00 (4.00–16.00) RmCYP51 A F1 1774 1533 510 Y 52 (n = 13) RmCYP51 B F5 1645 1539 508 F M. circinelloides 16.00 (16.00–>16.00) McCYP51 A F1 1773 1539 512 Y 57 (n = 18) McCYP51 B F5 1658 1533 510 F a VCZ susceptibility according to CLSI standard microbroth dilution method 54 ; ORF, open reading frame; LDM, lanosterol 14α-demethylase; MIC, minimum inhibitory concentration; b loci A and B were attributed according to identification with CYP51A and CYP51B of A. fumigatus strain AF293; P450 family name was attributed to each CYP51 paralogue according to Nelson’s database ( http://drnelson.utmem.edu/CytochromeP450.html ); d amino acid position 140 according to S. cerevisiae CYP51 ...…”
Section: Resultsmentioning
confidence: 99%
“…In vivo Drosophila melanogaster and mouse models of Mucorales infection showed that exposure to VCZ selectively enhanced virulence and significantly reduced survival rates of the model organisms, when compared to infection with a R. arrhizus strain not pre-exposed to VCZ 51 . Patients with pulmonary or splenic mucormycosis fail to respond to VCZ therapy 52 . All Mucorales species tested also showed in vitro resistance to the short-tailed triazoles TDM and FLC (median MICs: >16.00 mg/L and >64.00 mg/L, respectively), but variable susceptibility to the long-tailed triazole PCZ (2.00–8.00 mg/L) and the polyene amphotericin B (0.50–2.00 mg/L), demonstrating that Mucorales are resistant to short-tailed triazoles only.…”
Section: Discussionmentioning
confidence: 99%
“…The unacceptably high mortality rate, limited options for therapy and the extreme morbidity of highly disfiguring surgical therapy make it imperative to look for alternative strategies to treat and prevent these infections. While the genomes of some Mucorales isolates have been sequenced, there remains a paucity of genome data and comparative analyses for this group of fungal pathogens 11 16 17 18 19 20 21 22 23 24 25 . In this work, we utilize an integrated genomics approach to understand the population genetics, evolution and phylogeny of this understudied group of fungi, and identify potential therapeutic targets in the pathogen and the host.…”
mentioning
confidence: 99%
“…Structural and functional gene prediction followed the protocol previously described ( 14 16 ). For the phylogeny-based prediction, the proteomes of P. bilaiae , P. brevicompactum , P. chrysogenum , P. digitatum , P. glabrum , P. janthinellum , P. lanosocoeruleum , and P. raistrickii (all available at the Joint Genome Institute [JGI]) were mapped to the reference genome.…”
Section: Genome Announcementmentioning
confidence: 99%
“…For the phylogeny-based prediction, the proteomes of P. bilaiae , P. brevicompactum , P. chrysogenum , P. digitatum , P. glabrum , P. janthinellum , P. lanosocoeruleum , and P. raistrickii (all available at the Joint Genome Institute [JGI]) were mapped to the reference genome. In contrast to other reported studies ( 15 , 16 ), rRNA was removed from the RNA-Seq data using riboPicker ( 17 ). Functional annotations were obtained by using Blast2GO ( 18 ) and InterProScan ( 19 ) and included the prediction of secondary metabolite gene clusters using SMURF ( 20 ).…”
Section: Genome Announcementmentioning
confidence: 99%